Oracle JET for developers : implement client-side JavaScript efficiently for enterprise Oracle applications - Pattamsetti, Raja Malleswara Rao (Packt Publishing, 2017)
If you are a JavaScript developer looking to create resilient and robust client-side apps, then this book is the right choice for you. This book will give you a complete practical understanding of the Oracle JavaScript Extension Toolkit (JET) and how you can use it to develop efficient client-side applications with ease.